Zmiany afiliacji partyjnych w trakcie kadencji parlamentarnej a partyjne przywództwo populistyczne. Analiza porównawcza przypadków Czech, Litwy i Polski (Politeja, 2022)
LEGISLATIVE PARTY SWITCHING AND POPULIST PARTY LEADERSHIP: A COMPARATIVE ANALYSIS OF THE CZECH, LITHUANIAN, AND POLISH LEGISLATURESThe aim of this article is to empirically demonstrate whether parliamentary groups led by populist leaders are more likely to be affected by party switching than groups without populist leadership. On the basis of the data collected for nine terms of the Czech, Lithuanian and Polish parliaments (n = 2403 seats) it was proved that MPs were more than twice as likely to leave the parliamentary groups with populist leadership than the other groups. In addition, it was evidenced that three out of four MPs affiliated to the groups with populist leadership which found themselves in opposition to the government left their party during the parliamentary term and, in addition, most of these groups were dissolved before the end of the full parliamentary term.